py2PowerDEVS: Construction and Manipulation of Large Complex Structures for PowerDevs Models via Python Scripting - Pecker-Marcosig, Ezequiel; Bonaventura, Matias; Lanzarotti, Esteban; Santi, Lucio; Castro, Rodrigo (Proceedings - Winter Simulation Conference, 2022)
As the disciplines of modeling and simulation evolve and become more efficient, the complexity of the scientific applications that can be tackled by simulation modeling continue to increase. The approach of building complex models through the composition and interconnection of modular units of behavior has been a key factor in this success. However, very often complexity entails a significant growth in the size and intricacy on the structure of simulation models. In this paper we confer new capabilities for building models with large complex structures to PowerDEVS, an established C++-based simulation toolkit for the DEVS formalism, that has typically based its modular modeling experience on a Graphical User Interface. We present py2PowerDEVS, a Python framework that seamlessly integrates pre-built modular PowerDEVS components into the powerful and growing ecosystem of Python scripting, enabling the algorithmic design of large complex PowerDEVS model structures. We demonstrate the use of py2PowerDEVS in three scientific application domains: data networks, geographical virus spread and mechanical systems.